Rainfall Prediction in Palembang City Using the GRU and LSTM Methods - Surta, Wijaya; Tri Basuki, Kurniawan; Edi Surya, Negara; Yesi Novaria, Kunang (INTI International University, 2023)
Rainfall is one of the weather elements that are very important for the survival of an area. Palembang City, as one of the big cities in Indonesia, is heavily influenced by the level of rainfall that occurs every month. Variations in precipitation can affect various aspects of people's lives, such as agriculture, industry, tourism, etc. Accurate rainfall predictions can assist in preparing for multiple activities and making the right decisions. Therefore, it is crucial to research predicting rainfall in Palembang. It is expected to simplify the prediction process and produce more accurate results. This research uses the Gated Recurrent Unit (GRU) and Long-Shorted Term Memory (LSTM) methods to make daily rainfall predictions for the next month using weather element data for ten (10) years in Palembang, utilizing the deep learning method. The hyperparameter model tuning experiment was conducted to obtain the best prediction results. From the research results, it can be concluded that the LSTM model is overall better than the GRU model in predicting daily rainfall in Palembang City. GRU has RMSE 9.33 and R2 0.54, while the LSTM Model has RMSE 7.45 and R2 0.70.